NOODIVERSITY, TECHNODIVERSITY: elements of a new economic foundation based on a new foundation for theoretical computer science. Issue 4 (3rd July 2020) - Stiegler, Bernard; Ross, Daniel
Abstract: Today's question concerning technology involves asking about both the post-pandemic world and the post-data-economy world, in a situation where resentments and scapegoats are easily generated. We can no longer avoid integrating this question with that of entropy, but also with the specific question of anthropic entropy, and the way this has accompanied the rise of computation: it thus demands a new approach to theoretical computer science. While digital and network technologies initially seemed to offer new hopes for the reorganization of work (exemplified by the free software movement), the subsequent rise of smartphones and social networks seems to have turned these hopes into lost illusions: network effects and algorithmic platforms are hegemonic, and the changes brought by neoliberalism are being progressively intensified. Unless something utterly improbable happens, this dystopian tendency seems destined to continue. Could the pandemic bring the necessary break? Before asking this question, we should reflect on the meaning of the probable, the improbable and the unforeseen. Capitalism can be described as an epistēmē, whose operator is information, but also as an anti- epistēmē, because it installs generalized proletarianization. In other words, knowledge is destroyed and diversity systemically eliminated, and a new theoretical computer science must learn how to take the need for diversity functionally into account. Yuk Hui raises these questions through the notion of technodiversity, as a way of challenging the hegemony of a universal calculability prescribing arrangements between the technical system and the social and biological systems. Today, the computer is a cellular element in a global megamachine, and, from Hui's perspective, it imposes this cosmotechnical question firstly because China cannot be reduced to the West. Already in the twentieth century, the culture industries tended to reduce reason to rationalization, raising the question of whether modernity is the generalization of the universal or its elimination. What lies behind this question is Leroi-Gourhan's notion of universal technical tendencies. For Leroi-Gourhan, this question involves three kinds of milieus – interior, exterior and technical – and these are mutually diffracting, which means: there is never a milieu, but only milieu s . We must further distinguish the production of technical organs (exosomatic exorganogenesis) from the production of those specifically concerned with memory (exomnesic exorganogenesis). The conditions of the expression of universal technical tendencies vary according to advances in exomemorization. Tendencies play out in an irreducible way with counter-tendencies, forming open dynamic systems. Today, platforms tend to eliminate this play, and this is why today's state of fact inherently calls for the question of diversity. The challenge is to introduce new conditions for variability, reconstituting noodiversity. The exosomatic technical milieu is in excess over the interior milieu, connecting interior milieus together by traversing the common exterior milieu. Today, this traversal of the technical saturates the exterior milieu. Exomnesic exorganogenesis involves a meeting of three layers – the physiological, the nervous and the logical – where the second and third of these are what must be woven in new ways by a new theoretical computer science opening up new forms of différance between the understanding and reason.